ANALYSIS OF SOCIAL AND ENVIRONMENTALLY CONSCIOUS BEHAVIOR AS PART IN COMPANIES - Viktória Vida; Maryam Alhassan Talatu (Apstract: Applied Studies in Agribusiness and Commerce)
This research estimates public perceptions of corporate environmental responsibility and the use of clean energy in terms of how businesses exhibit environmentally sensitive behaviour through their operations and how clean energy is used within daily business operations. It carries out a large-scale survey among 100 participants, analyzing responses across various dimensions of corporate social responsibility, especially those relevant to environmental practices. The findings show that there is a high public expectation of business environmental responsibility, as 82% of the respondents regard it as very important for companies to undertake social responsibility activities. The same percentage (80%) feel it is essential that companies be liable for environmental damage. The same study also firmly focused on carbon emission reduction since 91% rated it somewhat or very important for companies to reduce their carbon emissions.